Feminist Buddhism as Praxis: Women in Traditional Buddhism - Kawahashi, Noriko (Japanese journal of religious studies, 2003)
This paper discusses a project the author has been engaged in since 1994 with women in the Japanese Buddhist community who are working across sectarian boundaries to recreate a Buddhism that goes beyond patriarchy. While the celibacy prized by many Buddhist orders that profess renunciation of secular married life has resulted in oppression of women, this paper points out that women face similar problems even in the laicized Shin school. The paper describes various perspectives that women of this project have adopted in their feminist critiques of Buddhism and their movement to remake Buddhism for today, and argues that the question of whether traditional Buddhist orders can overcome their predicament depends upon whether the men can open themselves to hear the women's voices of protest. The paper shows that this project can also contribute to a critique of the Eurocentric feminist version of Buddhism that informs the understanding of some European and American feminist scholars in this field.